Dictatorship, Disorder and Decline in Myanmar - Skidmore, Monique (ANU Press, 2008)
Mass peaceful protests in Myanmar/Burma in 2007 drew the world's attention to the ongoing problems faced by this country and its oppressed people. In this publication, experts from around the world analyse the reasons for these recent political upheavals, explain how the country's economy, education and health sectors are in perceptible decline, and identify the underlying authoritarian pressures that characterise Myanmar/Burma's military regime.